Strengthening Chemistry Learning Outcomes through Discovery Learning and Laboratory Activities on Colloidal Systems Material - Hilmina, Hilmina; Ahmad, Abu (Cahaya Ilmu Cendekia Publisher, 2024)
Purpose of the study: This research aims to improve students' chemistry learning outcomes using the discovery method through laboratory activities on the concept of colloidal systems. Methodology: The method used in this study was classroom action research with a sample of 33 students taught using the discovery method through laboratory activities. The classroom action research consisted of two research cycles, each with stages including planning, implementation, observation, and reflection. The research instruments used were observation sheets, questionnaires, learning outcome tests, and teacher and student interviews. Main Findings: From the results of this thesis research, it is obtained an overview that this research has achieved the criteria that have become the limit of success indicators shown through the increase in the category of aspects of active student participation in learning in each cycle. Likewise, the learning outcome test saw an increase in the average score in cycle I of 68.09 increasing to 74.81 and no more students received a score below 60.00. Similarly, the results of student interviews responded positively to the learning process using the discovery method through laboratory activities. Novelty/Originality of this study: This research offers novelty through the integration of discovery learning methods with structured laboratory activities on the concept of colloidal systems to improve student learning outcomes. This approach emphasizes active student engagement through experimentation and problem-solving. These findings complement previous studies by demonstrating the effectiveness of the combination of inquiry learning and practicum in improving conceptual understanding and student participation.